DESKRIPSI PEMAHAMAN KONSEP MATERI ASAM-BASA SISWA KELAS XI MIPA 1 MAN 2 PONTIANAK - Septiyani, Sarah; Sartika, Rody Putra; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe main goal of this study was to describe the conceptual understanding and several causes of learning difficulties of students in MAN 2 Pontianak. Subjects in this study were students of class XI MIPA 1 which consists of 40 people. The form of this research were descriptive research with case study research type. The instruments used were essay test concept comprehension and interview. The data analysis technique used were the assessment of concept comprehension test and interview. The result of this study indicated that Â percentage of students' understanding level of MAN 2 Pontianak concept on acidic bases with very good category, good, enough, less and very less shows the percentage of 10%, 33%, 25%, 23% and 10%. There were several causes of learning difficulties that the students had such as lack of self-motivation, many extracurricular, teaching methods provided by the teacher are not attractive and students didnâ€™t study at home.Â Keywords: Conceptual Understanding, Acid-Base, Several Causes of Learning Difficulties